Semantic web services : (Springer, 2007)
Semantic Web services combine Web services communication technology with the intelligent processing of ontology-based metadata to achieve highly integrated enterprise application integration scenarios, for service look-up, schema matching, or protocol negotiation, for example. Rudi Studer and his team deliver a self-contained compendium about this exciting field, starting with the basic standards and technologies and also including advanced applications in eGovernment and eHealth. The contributions provide both the theoretical background and the practical knowledge necessary to understand the essential ideas and to design new cutting-edge applications. They address computer science students as well as researchers in academia and industry who need a concise introduction and state-of-the-art survey of current research, and the book can easily be used as the basis of a specialized course on Web services or Semantic Web applications. In addition, IT professionals will be able to assess the potential and possible benefits of this new technology.